2013
DOI: 10.1002/j.1532-2149.2013.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of excess subcutaneous fat in pain and sensory sensitivity in obesity

Abstract: Obese participants are less sensitive than non-obese individuals, but only on areas with excess subcutaneous fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 62 publications
4
76
4
2
Order By: Relevance
“…Independent of exercise, Price et al has shown no difference in CPM efficiency between obese and normal weight adults using a test site with little excess subcutaneous fat (forehead). 18 Previously, we have shown in adolescents that lean mass was related to both the CPM and EIH responses; lean mass of the arm uniquely predicted 10% of the CPM magnitude and lean mass of the body was correlated with the EIH magnitude. 4,13 Despite previous research showing that lean mass was related to both CPM and EIH independently, lean mass does not appear to account for the relation between CPM and EIH.…”
Section: Discussionmentioning
confidence: 84%
“…Independent of exercise, Price et al has shown no difference in CPM efficiency between obese and normal weight adults using a test site with little excess subcutaneous fat (forehead). 18 Previously, we have shown in adolescents that lean mass was related to both the CPM and EIH responses; lean mass of the arm uniquely predicted 10% of the CPM magnitude and lean mass of the body was correlated with the EIH magnitude. 4,13 Despite previous research showing that lean mass was related to both CPM and EIH independently, lean mass does not appear to account for the relation between CPM and EIH.…”
Section: Discussionmentioning
confidence: 84%
“…Until now, no study has shown a correlation between visceral pain and BMI. [16][17][18] We would like to emphasize that the data in this current study did not address other etiologies of renal colic, e.g., renal infarction or malignancy. Primary imaging with sonography and plain radiography had been performed for the 171 patients in our study.…”
Section: Discussionmentioning
confidence: 96%
“…25 Experimental evidence showed peripheral pain sensitivity aberrations and central sensitization in obese compared with nonobese subjects, but the relationship remains the subject of debate. 126,127 Recently, mechanical factors were brought to the fore when neuropathic knee pain was explained, in part, by turning the innocuous input from high-threshold mechanoreceptors (AÎČ-fibers) into painful sensations during joint load. 39 …”
Section: Shared Mechanism Of Obesity and Neuropathic Painmentioning
confidence: 99%